Synthesis of stemofoline analogues as acetylcholinesterase inhibitors - Kwankamol Sastraruji (2018)
Thirty-two new stemofoline analogues were prepared from didehydrostemofoline for studies as AChE inhibitors. C-3 Side-chain modified amino, carbamate, triazole and oxazole stemofoline derivatives were prepared. In general the amine derivatives were found to be stronger inhibitors of AChE than their alcohol analogues that we previously reported. Compounds 5 and 26, with small C-3 side-chain substituents, were two of the most active inhibitors. Preliminary molecular docking studies suggested that these compounds may inhibit AChE by binding horizontally along the passage of the active-site gorge and block access to acetylcholine. © 2012 Elsevier Ltd. All rights reserved.